ENHANCE SMART PROTECTION BATTERY DAMAGE AIRCRAFT BASED ON RCA METHOD - Muhammad Yunus Lubis; Amani Darma Tarigan; Dicky Lesmana (Jurnal Scientia, 2023)
Airplane is one of the most popular transportation in Indonesia, one of the aircraft types is Boeing B777-200/300 Next Generation. In addition to being faster than other modes of transportation, aircraft have the lowest accident rate among other modes of transportation, but also have a low percentage rate of life chances in the event of an accident. Therefore, aircraft must have reliable systems that are proven by testing, one of which is the backup electrical system. This research aims to examine how the backup electrical system on the Boeing 777 Next Generation works, and conduct research on the reliability of the backup electrical system on the Boeing 777 Next Generation by calculating the battery life on the aircraft which is the source of electricity for backup electricity. The research methods used include literature study, data collection from sources, and data analysis. The data collected are the overall Boeing 777 Next Generation electrical system data, backup electrical data, and backup electrical system component data and specifications. The results of this study indicate that the backup electrical system studied (Boeing 777 Next generation Block Number 200 and 300) has specifications that are in accordance with the applicable regulations in Indonesia contained in the Civil Aviation Safety Regulation Chapter.